Carriage of adhesive Escherichia coli after restorative proctocolectomy and pouch anal anastomosis: relation with functional outcome and inflammation. Issue 10 (October 1993) - Lobo, A J; Sagar, P M; Rothwell, J; Quirke, P; Godwin, P; Johnston, D; Axon, A T
Abstract : Restorative proctocolectomy with pelvic ileal reservoir is a well accepted option for the surgical treatment of ulcerative colitis. Acute pouchitis is a common complication and resembles acute ulcerative colitis. Patients with ulcerative colitis carry Escherichia coli that adhere to epithelial cells and thus this study examined whether acute pouchitis is associated with the carriage of adhesive E coli. E coli isolated from stool samples from 24 patients (median age 34 years, range 16-64; 13 men, 11 women) who had had restorative proctocolectomy with pelvic ileal reservoir were examined by means of the buccal epithelial cell adhesion assay. Patients were studied at a median of 12 months (range 7-21) after operation. Eight of 24 patients had acute pouchitis at the time of study. Adhesive E coli were detected in nine of 24 patients with a pelvic ileal reservoir compared with none of 12 controls (p < 0.05). The buccal epithelial cell adhesion index was inversely related to the degree of acute pouchitis (rs = 0.46, p = 0.024) and to the functional outcome (rs = -0.49, p = 0.022). Carriage of adhesive E coli was not related to the design of the reservoir. By contrast with ulcerative colitis, acute pouchitis is not associated with the carriage of adhesive E coli.